Le rôle de l'enseignant dans les interactions en classe de FLE : analyse de cas sur les pratiques enseignantes en classe avec le public coréen - Eunja Lee (Nantes Université, 2017)
The purpose of this study is to (re) define the role of the teacher in oral interactions in FLE classes in South Korea. The analysis of teaching practices in general French (level A0-A1) has shown the diversity of professional practices developed to accomplish, in this specific context, the different teaching functions. Our focus is on strategies for implementing a "hybrid" teaching methodology for Korean learners, including : use of the learners' mother tongue ; the application of techniques deriving from the traditional language teaching approach still in force in South Korea (translation, oral reading, direct repetition of important sentences or textbook conversations and individual questions on the contents of the conversation) ; and the application of certain methods within the communicative and action-based approaches. The final objective of this study is to analyze the teaching practices mentioned above and to determine which ones work and to try to offer contextualised instruction adapted to the Korean public.